Voltage instability analysis based on modal analysis technique and artificial neural network - Ahmad Fateh Mohamad Nor; Marizan Sulaiman (Institute of Advanced Engineering and Science, 2019)
One of the paramount importance in the operation of electrical power system operation order to sustain the equilibrium of the system is the stability of the load buses’ voltages. If the load buses voltages are not stable, this can cause serious problem especially power system blackout. This paper presents the analysis of voltage instability in electric power system by using modal analysis technique. However, one of the challenges of modal analysis is the intencive and complex calculation procedures. In order to overcome that, this paper implements Artificial Neural Network (ANN) to improve the implementation of modal analysis technique. ANN is used to determine the participation factors obtained from the modal analysis technique. The results show that modal analysis technique is able to show which bus is close towards experiencing voltage instability. In addition, the results also show that ANN is able to predict the values of participation factors. A load bus is considered a weak bus if the bus has high tendency towards experiencing voltage instability. IEEE-14 bus test power system has been chosen as the test power system.